ANALISIS HUKUM TERHADAP PELAKU TINDAK PIDANA PENYEBARLUASAN PORNOGRAFI MELALUI INTERNET DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Junita Yunara; Emilda Firdaus; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The problem of pornography has not been as expected, we can also seethis with the increasingly widespread spread of pornography through the internet.So that the Ministry of Communication and Information of the Republic ofIndonesia said it would block various pornographic websites. People can stillfreely distribute it on their respective social media such as Instagram, Twitter,Facebook and others. Before the existence of special regulations governingpornography itself, contained in Article 282 and 283 of the Criminal Code(KUHP), because there were still many deficiencies in the Criminal Code, LawNo. 11 of 2008 concerning Information and Electronic Transactions was alsodrafted. Law Number 44 of 2008 concerning Pornography.This type of research is normative legal research, known as